PROTEROZOIC TECTONO-MAGMATIC ACTIVISATION AND GOLD MINERALISATION IN WESTERN PART OF KIROVOGRADSK BLOCK (OVRAZHNY ORE MANIFESTATION OF LYPNIZHKA STRUCTURE AS AN EXAMPLE) - HRINCHENKO, O.; BONDARENKO, S.; IVANOV, B.; SOMKA, V.; RIABOKIN, V.; BONDARENKO, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article discusses data on common mechanism of ore formation in Lypnyazka structure, that caused by regional processes of tectono-magmatic activization at 2000 ± 100 Ma. Proterozoic activization resulted in bulk mobilisation and migration of ore forming elements from sites of magma generation to the exocontact zones of carbonaceous metamorphic rocks distribution.